Revisiting tropical peatlands in Indonesia: Semi-detailed mapping, extent and depth distribution assessment - Anda, Markus; Ritung, Sofyan; Suryani, Erna; Sukarman; Hikmat, Muhammad; Yatno, Edi; Mulyani, Anny; Subandiono, Rudi Eko; Suratman; Husnain (Geoderma, 2021)
[Display omitted] •New detail spatial peatland information in Indonesia covers 13.43 million ha.•The new peatland areas and thickness are results of semi-detail mappings.•New peatland mapping area is smaller than previous estimates 15–27 million ha.•The peatland varied from 50 to 1050 cm deep with 50–300 cm is dominant (69%)•The new detail peatland data allow C stock accuracy, future use and management. A detailed spatial inventory of the extent and depth distribution for tropical peatlands is not currently available; however, there is a critical need for new detailed peatland information at national, regional and global scales. Hence, the objective of this study was to provide a rigorous assessment of the extent and depth distribution of tropical peatlands in Indonesia. Data were acquired using a standard method protocol of semi-detailed peatland mapping programs (1:50 000 scale) from 2013 to 2019 for all Indonesian peatlands. Arc-GIS and multi-source satellite images (Landsat ETM-7, Landsat 8 OLI, ALOS, SPOT-5 and SPOT-6/7, and DEM/SRTM) were used to delineate soil-mapping units (polygons) which were supported by depth observation points derived from databases of soil maps 1:50 000 and peatland maps 1:250 000, and then subsequently verified with rigorous ground-truthing. Field transects were made between rivers using systematic distances to observe peat morphological features and thickness resulting in a total of 18,232 data points that included 14,185 new observations and 4,047 legacy points. Our results provide the first systematic census for all Indonesian peatlands and showed that peatlands occupied 13.43 million ha distributed on four islands (million ha): Sumatera (5.85) > Kalimantan (4.54) > Papua (3.01) > Sulawesi (0.024). Peat depth was classified into six categories: D1(50-<100 cm), D2 (100-<200 cm), D3 (200-<300 cm), D4 (300-<500 cm), D5 (500-<700 cm) and D6 (≥700 cm), which represented (million ha/peatlands%) 3.17 (24%), 3.44 (26%), 2.61 (19%), 2.32 (17%), 1.29 (10%) and 0.59 (4%), respectively. Exceptionally deep (≥700 cm) peatlands occurred on Kalimantan and Sumatera Islands, but were not found on Papua and Sulawesi Islands. The present peatland extent (13.43 million ha) was smaller than previous estimates (pre-2012) that varied from 14.9 to 27.0 million ha. The smaller peatland extent in the present semi-detailed mapping inventory (1:50 000) than previous estimates (pre-2012) may result primarily from (i) segregation of mineral soil inclusions previously considered as peatland, (ii) improved remote sensing and GIS tools (e.g., DEM/SRTM) that prevented misclassification of peatland areas, and (iii) extensive field observation for verification of peatland boundaries and thickness requirements (≥50 cm) that eliminated peatlands lost to enhanced decomposition from agricultural management and drainage practices. Our study on peatland extent and thickness provides new detailed information of tropical peatlands in Indonesia (a major region of tropical peatlands) to serve as a baseline for future inventories. The information provided by this study updates peat information for Indonesia (extent and depth), fills a critical knowledge gap for accurately determining regional/global organic C stocks, and informs future directions for the sustainable use and management of tropical peatlands.